Framing Sino-Venezuelan Oil Cooperation: Perspective from China - Shoujun CUI; Nan ZHOU (América Latina Hoy, 2019)
ABSTRACT: The cooperation between China and Venezuela is both strategic and complementary in nature, and has characteristics of a complex interdependency built on oil supply as the main axis and the ‘Loans for Oil’ model as a key dynamic background. With the oil price slump, China’s commercial presence in Venezuela is now faced with the potential risks of debt default, geopolitical unrest and possible u.s. interference. This article explores the trajectory, modalities, dynamics and risks of the China-Venezuela cooperation model through a Chinese perspective, which is regarded as a typical model of the South-South cooperation paradigm.